TINJAUAN IMPLEMENTASI HAK-HAK NORMATIF PEKERJA - Buwana, Sudibyo Aji Narendra; Santoso, Aris Prio Agus; Guntara, Peter (Collegium Studiosum Journal, 2025)
Workers' normative rights are one of human rights on nickel mining company. The formulation of the problem is how the implementation of the normative rights of workers on national strategic projects while the purpose of the research is to analyse the implementation of the rights of workers on national strategic projects. The type of research used by researchers in this study is empirical juridical. The research approach used in this research is a juridical sociological approach. Data collection techniques using in-depth interviews and observation. All primary and secondary data in this study were collected and analysed qualitatively. The results show that the implementation of workers' normative rights has been well implemented. The conclusion is that the implementation of normative rights in national strategic projects has gone well. This is evidenced by the fact that the national strategic project has fulfilled the normative rights of workers, including the right to wages based on UMP, the provision of THR rights, the right to menstrual/haid leave, the right to maternity leave, the right to miscarriage leave, the right to special facilities at certain hours for female workers, the right to annual leave, the right to sabbatical leave, the right to roster leave for workers from outside the area, the right to leave work with pay, the right to special facilities at certain hours for female workers, the right to occupational safety & health, the right to get BPJS Employment benefits JHT, JKK, JK, JP, and the right to health maintenance insurance.